2009
DOI: 10.1007/s10802-009-9306-4
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Anxiety and Depression in a Normative Sample of Younger and Older Australian Adolescents

Abstract: It has been reported that depression and anxiety have overlapping symptoms and are conceptually interrelated. One of the most prominent theoretical developments that explain this association is Clark and Watson's tripartite model (Journal of Abnormal Psychology, 100:316-336, 1991) that posits these two disorders and negative emotions share a latent component of negative affect (NA). The current study had two aims, (a) to compare a tripartite factor structure against competing models by Confirmatory Factor Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
130
7
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 52 publications
18
130
7
9
Order By: Relevance
“…Confirmatory factor analysis supports a uniform structure, high internal consistency, [23][24][25][26] and temporal stability at 3 to 8 years follow-up. 27 Patient anxiety symptoms were of particular interest to the present study, and the DASS anxiety scale consists of 4 subscales, 2 of which capture somatic symptomatology, and 2 of which capture cognitive symptomatology.…”
Section: Psychological Distressmentioning
confidence: 66%
“…Confirmatory factor analysis supports a uniform structure, high internal consistency, [23][24][25][26] and temporal stability at 3 to 8 years follow-up. 27 Patient anxiety symptoms were of particular interest to the present study, and the DASS anxiety scale consists of 4 subscales, 2 of which capture somatic symptomatology, and 2 of which capture cognitive symptomatology.…”
Section: Psychological Distressmentioning
confidence: 66%
“…Each subscale contains 7 items, and each item is scored on a 4-point Likert scale ranging from 1 (did not apply to me at all) to 5 (applied to me very much of the time), reflecting the extent to which the respondent has experienced over the past week. Numerous studies have found support for reliability, validity and factor structure of the DASS-21 (e.g., Antony et al 1998;Gloster et al 2008;Norton 2007;Szabó 2010;Tully et al 2009;Willemsen et al 2011). The Chinese version of the DASS-21 was translated via a two-stage process of translation and back translation (Taouk et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…While there is some evidence for the tripartite model in child samples (e.g., Chorpita and Daleiden 2002;Chorpita et al 2000b;Tully et al 2009), these studies are limited in that they aggregated the anxiety disorders into a single factor as opposed to assessing discrete anxiety disorders and/or they did not use DSMbased anxiety and mood symptoms. Also, review of the articles reveals that many investigators studying diagnostic co-occurrence focus on structures that are strictly data driven as opposed to using a priori examination of theoretical models.…”
Section: Child Modelsmentioning
confidence: 99%